2018
DOI: 10.1371/journal.pone.0194174
|View full text |Cite
|
Sign up to set email alerts
|

Noise pollution limits metal bioaccumulation and growth rate in a filter feeder, the Pacific oyster Magallana gigas

Abstract: Shipping has increased dramatically in recent decades and oysters can hear them. We studied the interaction between noise pollution and trace metal contamination in the oyster Magallana gigas. Four oyster-groups were studied during a 14-day exposure period. Two were exposed to cadmium in the presence of cargo ship-noise ([Cd++]w ≈ 0.5 μg∙L-1; maximum sound pressure level 150 dBrms re 1 μPa), and 2 were exposed only to cadmium. The Cd concentration in the gills ([Cd]g) and the digestive gland ([Cd]dg), the valv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 57 publications
7
20
2
3
Order By: Relevance
“…Manuscript to be reviewed (Wright et al 2007). Previous studies have shown the adverse effects of anthropogenic noise on bivalves' physiological processes such as metabolism and growth rate (Roberts et al 2015;Peng et al 2016;Charifi et al 2018;Shi et al 2019). Thus, our results add to previous studies in assessing whether the affected physiological processes in bivalves are the result of anthropogenic noise-based distraction.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Manuscript to be reviewed (Wright et al 2007). Previous studies have shown the adverse effects of anthropogenic noise on bivalves' physiological processes such as metabolism and growth rate (Roberts et al 2015;Peng et al 2016;Charifi et al 2018;Shi et al 2019). Thus, our results add to previous studies in assessing whether the affected physiological processes in bivalves are the result of anthropogenic noise-based distraction.…”
Section: Discussionsupporting
confidence: 69%
“…Manuscript to be reviewed 2016). Their palps also allow them to sense pressure changes from underwater sound waves and bivalves have been documented to significantly react to changes in underwater acoustic stimuli (e.g., Mosher 1972;Peng et al 2016;Shi et al 2019;Charifi et al 2018;Roberts et al 2015). Anthropogenic noise is one such external stimulus that could distract bivalves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-and ecosystem-wide effects may occur whenever MNP affects species that have crucial roles, such as habitat-former mollusks (e.g. oysters; Charifi et al, 2018) and high-level fish predators (Guidetti, 2006;Sarà et al, 2007).…”
Section: Conclusion Knowledge Gaps and Perspectivesmentioning
confidence: 99%
“…Bij langdurige blootstelling van Japanse oesters aan scheepvaartgeluid (14 dagen) was een verminderde activiteit (o.a. filtratie, klepbeweging) en groei waargenomen (Charifi et al, 2018). Er is bij de mantelschelp Pecten fumatus geen directe massale sterfte waargenomen maar wel een verhoogde mortaliteit in de periode na blootstelling aan het geluid.…”
Section: Samenvattingunclassified